2012
DOI: 10.1177/0091270011398867
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Adverse Drug Reactions in a South Indian Tertiary Care Teaching Hospital

Abstract: In India, very few reports on the cost of adverse drug reactions (ADRs) are available. There is a need to study this aspect of health care in order to understand the economic burden imposed by ADRs. The aim of the current work was to study the costs associated with documented ADRs in a tertiary care teaching hospital. This study was conducted in medical wards of a south Indian tertiary care teaching hospital over a 6-month period. The study protocol was assessed and approved by the institutional ethics committ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 35 publications
(63 reference statements)
4
37
2
Order By: Relevance
“…18 The most common serious reaction was extrapyramidal symptoms in this study that is in contrast with the previous studies showing pancytopenia 15 and StevensJohnson syndrome (SJS). 21 In line with the previous study, most reactions had subacute and latent onset.…”
Section: 1921contrasting
confidence: 95%
See 2 more Smart Citations
“…18 The most common serious reaction was extrapyramidal symptoms in this study that is in contrast with the previous studies showing pancytopenia 15 and StevensJohnson syndrome (SJS). 21 In line with the previous study, most reactions had subacute and latent onset.…”
Section: 1921contrasting
confidence: 95%
“…15,16,20 However, Jose and Rao observed similar incidence of 0.15% for both genders. 19 The adults showed high frequency of reactions, which is in concurrent with the studies by Venkatesan et al, 17 Rajkannan et al 18 and Rao et al 20 but differed from Ramesh et al 15 and Arulmani et al 16 showing high incidence in elderly.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…[1][2][3][4] Amongst the total ADRs, 0.2% to 41.3% lead to emergency hospitalizations worldwide and 28.9% of these ADRs are avertable. 5 Several studies have reported that misuse and irrational prescribing of drugs account for majority of ADRs.…”
Section: Introductionmentioning
confidence: 99%
“…5 Several studies have reported that misuse and irrational prescribing of drugs account for majority of ADRs. [1][2][3][4] India is one of the largest drug consuming countries in the world with substantial irrational prescribing and therefore increased likelihood of development of ADRs. 6 Thus, early identification and reporting of ADRs is extremely important from health and economical point of view.…”
Section: Introductionmentioning
confidence: 99%